2009
DOI: 10.1007/s00774-009-0141-z
|View full text |Cite
|
Sign up to set email alerts
|

Hop rho iso-alpha acids, berberine, vitamin D3 and vitamin K1 favorably impact biomarkers of bone turnover in postmenopausal women in a 14-week trial

Abstract: Osteoporosis is a major health issue facing postmenopausal women. Increased production of pro-inflammatory cytokines resulting from declining estrogen leads to increased bone resorption. Nutrition can have a positive impact on osteoporosis prevention and amelioration. The objective of this study was to investigate the impact of targeted phytochemicals and nutrients essential for bone health on bone turnover markers in healthy postmenopausal women. In this 14-week, single-blinded, 2-arm placebo-controlled pilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The treated women showed 31% mean reduction in serum osteocalcin (a marker of bone turnover) and 13% increase in serum 25‐hydroxyvitamin D (25(OH) D). Treatment with this supplemental regimen produced a more favorable bone biomarker profile (Holick et al, ). However, in this study berberine has been administered beside some other agents and diet modifications.…”
Section: Endocrinementioning
confidence: 99%
“…The treated women showed 31% mean reduction in serum osteocalcin (a marker of bone turnover) and 13% increase in serum 25‐hydroxyvitamin D (25(OH) D). Treatment with this supplemental regimen produced a more favorable bone biomarker profile (Holick et al, ). However, in this study berberine has been administered beside some other agents and diet modifications.…”
Section: Endocrinementioning
confidence: 99%
“…Seven of the nine studies identified as multi-nutrient interventions [130,[132][133][134][135][136][137] reported on IGF-1, suggesting little or no effect (MD: 0.60 nmol/L, 95% CI −1.12 to 2.33, I2 0%, 519 participants, Figure 6). Effects did not differ in fixed-effects meta-analysis (MD: 0.60 nmol/L, 95% CI −1.12 to 2.33), suggesting that small study bias is not an issue here.…”
Section: Effects Of Multi-nutrient Supplements On Igf-1mentioning
confidence: 99%
“…For multi-nutrient interventions the composition of the nutrients varied substantially [130,[132][133][134][135][136] with some containing more than 20 different micronutrients [132,137], making it difficult to attribute benefit to any specific micronutrient. A number of studies also included additional protein making it difficult to isolate any specific effects of micronutrients from those of protein [61,132,137,144,145].…”
Section: Limitations Of the Available Datamentioning
confidence: 99%
“…One of the most prominent physiological effects of the hormonal decline associated with menopause is the loss of bone mass ultimately leading to osteoporosis. It has been shown that in addition to hop-derived rho iso-alpha acids [20,21], all major hop flavanones 8-PN, 6-PN, XH, and IXH possess E2-like effects on osteogenic differentiation in vitro [22]. Concerning the in vivo situation, one of the first publications on 8-PN elucidated its effect on bone mineral density (BMD) of ovariectomized (ovx) rats following 14 days of treatment.…”
Section: Effectiveness Of Hop Flavanones In Preventing Osteoporosismentioning
confidence: 99%